Combination of venetoclax with CHG regimen in refractory/relapsed T-lymphoblastic lymphoma/acute lymphoblastic leukemia: a case series and literature review - Mei Zhou; Yuze Yang; Xiaoyan Zhang; Yijie Jiao; Zhenxing Guo (Discover Oncology)
Abstract T lymphoblastic lymphoma/acute lymphoblastic leukemia (T-LBL/ALL) is a highly aggressive hematologic malignancy, with particularly poor outcomes for refractory/relapsed (R/R) patients. This article reports the efficacy and safety of V-CHG regimen (Venetoclax, cytarabine, homoharringtonine, G-CSF) in the treatment of three R/R T-LBL/ALL cases. One 69 years old female patient with T-ALL experienced a twice relapse and achieved morphological complete remission (CR) with one cycle of V-CHG regimen. Another 65 years old female patient with T-LBL progressed to T-ALL after continuous CR for 10 months and failed by two different salvage chemotherapy regimens. She achieved minimal residual disease (MRD) negative CR with a third-line treatment based on V-CHG regimen. The third T-ALL patient was a 26 years old male who resistant to VDCP induction regimen and achieved morphological CR with one cycle of V-CHG regimen, and obtained MRD negative CR after second cycle treatment. All the three patients were well tolerated to the V-CHG regimen. The results of this study indicate that the V-CHG regimen is effective and safe for R/R T-LBL/ALL, warranting further application in the future.